EKRANISASI CERPEN “الأسد الجائع” KE DALAM FILM “الأسد الجائع” KARYA QISHASHU AL JADDAH - Rofiqi Rofiqi (Universitas Muhammadiyah Gorontalo, 2025)
Whitewashing of written literary works is a common occurrence in society these days. This practice is commonly referred to as